Determinan Nilai Perusahaan: Peran Mediasi dan Moderasi Faktor Lingkungan pada Perusahaan Manufaktur Indonesia - Merry Anna Napitupulu; Junika Napitupulu; Septony B. Siahaan; Darusalam (Jurnal Ilmiah METHONOMI, 2026)
This study examines the effects of green innovation (GI), environmental performance (EP), and institutional ownership (KI) on firm value, with carbon emission disclosure (CED), green reputation (GR), and cost of capital (WACC) as parallel mediating variables, and media exposure (ME) and pollutive industry intensity (PI) as moderating variables. Using panel data from 43 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for 2021-2025 (215 firm-year observations), the study employs Structural Equation Modeling-Partial Least Squares (SEM-PLS) via SmartPLS 4.0 with 5,000-subsample bootstrapping. Results show: (1) green innovation and environmental performance positively and significantly affect all three mediators; (2) CED, GR, and WACC partially mediate the effects of GI and EP on firm value; (3) media exposure strengthens the CED-firm value relationship; and (4) pollutive industry intensity strengthens the effects of GI, EP, and CED on firm value. Institutional ownership has no significant direct effect on firm value (beta = 0.089; p = 0.217), a pattern plausibly linked to weaker monitoring incentives among diversified institutional investors in this emerging market. The final structural model explains 71.2% of the variance in firm value (R2 = 0.712). To the best of the authors' knowledge, this study is among the first to simultaneously test a three-channel parallel mediation model with double moderation in Indonesia's post-IDXCarbon (2023) capital market context.